Question
upstudy study bank question image url

Solve the equation. \[ \frac{2 x}{x-2}=5+\frac{13 x^{2}}{x-2} \]

Ask by Stuart Gonzalez. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x = \frac{10}{13} \) and \( x = -1 \).

Solution

To solve the equation: \[ \frac{2x}{x-2} = 5 + \frac{13x^2}{x-2} \] **Step 1: Combine the Fractions** First, subtract \(5\) from both sides to group the terms with the common denominator: \[ \frac{2x}{x-2} - 5 = \frac{13x^2}{x-2} \] To combine the fractions, express \(5\) with the common denominator \(x - 2\): \[ \frac{2x}{x-2} - \frac{5(x-2)}{x-2} = \frac{13x^2}{x-2} \] Now, combine the numerators: \[ \frac{2x - 5(x - 2)}{x-2} = \frac{13x^2}{x-2} \] Simplify the numerator: \[ 2x - 5x + 10 = -3x + 10 \] So the equation becomes: \[ \frac{-3x + 10}{x-2} = \frac{13x^2}{x-2} \] **Step 2: Eliminate the Denominator** Since \(x \neq 2\) (to avoid division by zero), multiply both sides by \(x - 2\): \[ -3x + 10 = 13x^2 \] **Step 3: Rearrange into Standard Quadratic Form** Bring all terms to one side: \[ 13x^2 + 3x - 10 = 0 \] **Step 4: Solve the Quadratic Equation** Use the quadratic formula \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\), where \(a = 13\), \(b = 3\), and \(c = -10\): \[ x = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 13 \cdot (-10)}}{2 \cdot 13} = \frac{-3 \pm \sqrt{529}}{26} = \frac{-3 \pm 23}{26} \] This gives two solutions: \[ x = \frac{20}{26} = \frac{10}{13} \quad \text{and} \quad x = \frac{-26}{26} = -1 \] **Step 5: Verify the Solutions** Ensure that neither solution makes the denominator \(x - 2\) zero. Both \(x = \frac{10}{13}\) and \(x = -1\) satisfy this condition. **Final Answer:** The solutions are \( x = \dfrac{10}{13} \) and \( x = -1 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Bonus Knowledge

To solve the equation \[ \frac{2 x}{x-2}=5+\frac{13 x^{2}}{x-2}, \] let's start by getting rid of the denominator. Multiply both sides by \(x - 2\) (assuming \(x \neq 2\)): \[ 2x = 5(x - 2) + 13x^2. \] Now, distribute the \(5\) on the right side: \[ 2x = 5x - 10 + 13x^2. \] Next, rearrange the equation to get everything on one side: \[ 0 = 13x^2 + 5x - 10 - 2x, \] which simplifies to: \[ 0 = 13x^2 + 3x - 10. \] Now we can solve this quadratic equation using the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}, \] where \(a = 13\), \(b = 3\), and \(c = -10\). Calculate the discriminant: \[ b^2 - 4ac = 3^2 - 4 \cdot 13 \cdot (-10) = 9 + 520 = 529. \] Now substituting in the values: \[ x = \frac{-3 \pm \sqrt{529}}{2 \cdot 13} = \frac{-3 \pm 23}{26}. \] This gives us two potential solutions: \[ x = \frac{20}{26} = \frac{10}{13} \quad \text{and} \quad x = \frac{-26}{26} = -1. \] Thus, the solutions to the equation are: \[ \boxed{\frac{10}{13} \text{ and } -1}. \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy